Police chief turnover in Texas: Do institutional environments matter? - Li, Yudu (International journal of police science & management, 2025)
The field of organizational studies has extensively examined factors influencing the turnover and succession of public officers, yet limited attention has been given to chiefs of police. Using institutional theory as a framework, this study explores police chief turnover by focusing on the institutional environment and the relationships between police chiefs and key individuals and entities within their communities. Utilizing survey data collected from police chiefs attending mandatory training programs designed for new appointees, the analysis reveals that police chief turnover is substantially associated with the quality of relationships with key stakeholders within the institutional environments, both individually and collectively. In addition, control variables such as police performance, appointment path, tenure length, agency size, and municipal structure were analyzed. Policy implications are discussed.